Reliability And Validity Of Knowledge, Attitude, Practice, And Perception (KAP2) Questionnaire On Food Poisoning And Its Prevention Among Consumers In Bangi And Kajang, Selangor, Malaysia - Mamot, M.; Mohamed, N. A.; Mohd Rani, M. D; Osman, M.; Mohd Zulkefli, N. A.; Sekawi, Z.; Awang Hamat, R. (Universiti Putra Malaysia, 2024)
Indexed by Scopus